THE INFLUENCE OF CONVERSATIONAL MARKETING STRATEGY ON CONSUMER PURCHASE DECISIONS AT CAHAYA BOLU SHOP, NORTH TORAJA REGENCY - Palili, Mariani; Pali, Elisabet; Kurniasari Wibisono, Lisa (JURNAL EKBIS, 2025)
Mariani Palili, 2025: The Influence of Conversational Marketing Strategy on Consumer Purchasing Decisions at Cahaya Bolu Shop, North Toraja Regency.The purpose of the study was to determine the effect of Conversational Marketing Strategy on Consumer Purchasing Decisions at Cahaya Bolu Store, North Toraja Regency. The research method used in this study is quantitative research. Data analysis in this study includes simple linear regression, validity test, reliability test, normality test, heteroscedasticity, t test, R test2. The data processing method in this study is to use IBM SPSS Statistics version software. 26 which shows that 86.1% of purchasing decisions are influenced by conversational marketing at Cahaya Bolu shop in North Toraja Regency and the remaining 13.9% are influenced by other factors not examined in this study. The results of the t-test show that conversational marketing has an effect on purchasing decisions. This can be seen from the sig.t value of 0.001 <0.05 and the results of the coefficient of determination (R square) of 0.861 or 86.1%.